2015
DOI: 10.1111/rda.12481
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bovine Serum Albumin on Boar Sperm Quality During Liquid Storage at 17°C

Abstract: This study aimed to investigate the effects of bovine serum albumin (BSA) on boar sperm quality during liquid storage at 17°C. Boar semen samples were collected and diluted with Modena containing different concentrations (0, 1, 2, 3, 4, 5 and 6 g/l) of BSA, and sperm motility, plasma membrane integrity, acrosome integrity, total antioxidative capacity (T-AOC) activity and malondialdehyde (MDA) content were measured and analysed. The results showed that Modena supplemented with 3, 4 and 5 g/l BSA could improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 34 publications
1
50
0
1
Order By: Relevance
“…Many studies have demonstrated that preservation of boar spermatozoa for long periods requires a decrease in their metabolic activity, which is achieved by dilution in an appropriate medium and lowering the temperature to 15-17°C (Johnson et al, 2000). In addition, acidic or hypoxic environments can reduce sperm metabolism (Zhang et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have demonstrated that preservation of boar spermatozoa for long periods requires a decrease in their metabolic activity, which is achieved by dilution in an appropriate medium and lowering the temperature to 15-17°C (Johnson et al, 2000). In addition, acidic or hypoxic environments can reduce sperm metabolism (Zhang et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The samples were transferred to the laboratory within 2 h. After evaluating the quality of the fresh semen samples, they were centrifuged at 750xg for 3 min at 17°C. The supernatant was then removed, and the semen pellet was re-suspended at a concentration of 1.0Xg 10 8 spermatozoa/mL in modified Modena solution (Zhang et al, 2015). Finally, the semen samples were all stored in an incubator at 17°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of SDS-PAGE of the SCP extender (unpublished data) indicated an abundance of proteins with a molecular weight of 60-66 kDa. Earlier studies demonstrated that BSA-supplemented extenders (molecular weight of approximately 65-66 kDa) reduced oxidative stress and improved the quality of boar spermatozoa stored in a liquid state at 17 o C (Zhang et al 2015). It should be noted, however, that BSA in the semen extender effused cholesterol in the plasma membrane of sperm cells, which increased the levels of reactive oxygen species (ROS) (Radomil et al 2011, Lee andPark 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Alvarez and Storey (1995) reported that BSA is a very potent inhibitor of lipid peroxidation in the spermatozoa, and this type of damage reduces sperm motility. It was proven that BSA added to the Modena extender exhibits antioxidant properties, reduces oxidative stress, and enhances the quality of boar semen stored at a temperature of 17 o C (Zhang et al 2015). The content of antioxidants in the stored semen plays an important role in the survivability of the cryopreserved spermatozoa (Bilodeau et al 2000, Funahashi andSano 2005).…”
Section: Discussionmentioning
confidence: 99%